Correction of psychoemotional status in patients with chronic bacterial prostatitis - Kuz'menko, V V; Kuz'menko, A V; Kurnosova, N V (Terapevtic̆eskii arhiv, 2012)
To comparatively analyze the efficiency of combination treatment in patients with chronic prostatitis. Psychometric and psychological methods, such as the Hamilton depression rating scale and the Hamilton anxiety rating scale, determination of the types of an attitude toward illness, and the personality rating questionnaire, were used to examine 80 men with chronic bacterial prostatitis (CBP) who were allocated to 2 groups. A study group received levofloxacin in combination with adaptol for 10 days; a control group had antibacterial therapy only. The patients receiving adaptol were ascertained to have a more evident normalization of mental disorders, as shown by the scales, as lower scores: 4.9 +/- 0.6 for irritability, 5.7 +/- 0.6 for reactive aggression, 5.1 +/- 0.7 for shyness, and as a higher score (up to 5.2 +/- 1.3) for sociability (p < 0.05). There was a pronounced reduction in diurnal mood variations, which is indicative of relief of anxiety and depressive disorders. The use of adaptol in a dose of 500 mg thrice daily for 10 days as part of the combination treatment of patients with an exacerbation of CBP permits correction of the mental status and improves the quality of life of patients in a shorter period of treatment.